Analisis Kemampuan Komunikasi Matematis Siswa Lamban Belajar dalam Menyelesaikan Soal Bangun Datar - Supriadi, Nanang; Damayanti, Rani (Al-Jabar: Jurnal Pendidikan Matematika, 2016)
The purpose of this study is to find out how mathematical communication ability of students slow in learning to solve the problem of waking flat in SD Negeri 1 Sukamaju Abung semuli north Lampung. The research method used is descriptive research using qualitative approach. The result of the research can be concluded is that the students write communication is slower to learn better than oral communication, it can be seen from the result of the answer of the student who answer the correct bigger than the student answer that correct answer in oral communication. It is said that students are slow to learn to have limitations to talk or convey ideas so they are more silent or even just smiling.